2003
DOI: 10.1354/vp.40-3-283
|View full text |Cite
|
Sign up to set email alerts
|

Abscess-Forming Inflammatory Granulation Tissue with Gram- Positive Cocci and Prominent Eosinophil Infiltration in Cats: Possible Infection of Methicillin-resistant Staphylococcus

Abstract: Abstract. We occasionally encounter feline cervical or mesenteric lesions diagnosed histopathologically as abscess or inflammatory granulation tissue with eosinophil infiltration. Gram-positive cocci accompany the lesions. In the present study, such lesions obtained from 27 cats were examined to evaluate the histopathologic features and the nature of the causative bacteria. The average age was 7.3 Ϯ 3.5 years. No sex predilection was observed. Most frequent locations of the lesions included the abdominal cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
42
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 9 publications
3
42
0
Order By: Relevance
“…It is presumed that eosinophils cause the specific fibrosis of FGESF and play a key role in the pathogenesis of FGESF (Craig et al 2009;Suzuki et al 2013;Weissman et al 2013). Previously, bacterial or fungal infection has been considered to be involved in the pathogenesis of FGESF (Ozaki et al 2003;Grau-Roma et al 2014), but in subsequent cases, no pathogens were detected (Craig et al 2009;Suzuki et al 2013;Weissman et al 2013). In the most recent study bacteria were found in nine of 13 FGESF cases (Linton et al 2015).…”
mentioning
confidence: 99%
“…It is presumed that eosinophils cause the specific fibrosis of FGESF and play a key role in the pathogenesis of FGESF (Craig et al 2009;Suzuki et al 2013;Weissman et al 2013). Previously, bacterial or fungal infection has been considered to be involved in the pathogenesis of FGESF (Ozaki et al 2003;Grau-Roma et al 2014), but in subsequent cases, no pathogens were detected (Craig et al 2009;Suzuki et al 2013;Weissman et al 2013). In the most recent study bacteria were found in nine of 13 FGESF cases (Linton et al 2015).…”
mentioning
confidence: 99%
“…Histopathologic findings demonstrated ulcers and dermal granulation tissue with linearly arranged eosinophils, mast cells, neutrophils, and plasma cells between dense, homogeneous collagen bundles (sclerosing dermatitis). This pattern of inflammation is distinct from most staphylococcal infections of the skin, and it has been suggested that this uncommon histologic finding in cats is associated with methicillin-resistant staphylococcal infection ( 1 ). …”
mentioning
confidence: 99%
“…This disease has been reported in cats and pumas ( Puma concolor ) [2,3,4, 9]. The etiology of this disease is the infection (bacteria, fungi and nematodes), foreign body or unknown [2,3,4, 7, 9]. Macroscopically, the lesion is observed as an ulcerated intramural mass at the pyloric sphincter and the ileocecocolic junction [2,3,4, 9].…”
mentioning
confidence: 99%
“…Microscopically, all lesions include a very characteristic trabecular pattern of dense collagen with proliferation of the reactive large myofibroblasts. Many lesions also have numerous eosinophils and mast cells [2, 3, 7, 9]. In cats, the term ‘FGESF’ is considered appropriate based on these microscopic characteristics [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation